Antibiotic resistance pattern of bacteria isolated from outdoor patients in Dhaka city: a single center study - Khatun, Most Salma; Nahar, Saimun; Kabir, Md Shahidul (Stamford Journal of Microbiology, 2020)
Bacterial infections are often found to cause morbidity and mortality around the globe. Indiscriminate use of antibiotic for treatment of such infections is reported to cause selective pressure and increase in drug resistance. Emergence of antibiotic resistance is a growing concern for people of all age having bacterial infections. It is important to determine the trend of antibiotic resistance patterns of pathogenic bacteria isolated from clinical samples for appropriate treatment of patients. A retrospective study was conducted on patient samples collected from 1 July 2018 to 15 March 2019. A total of 500 urine, 136 blood, 120 stool, 172 swab, 90 Sputum and 60 pus samples were randomly collected from both male and female patients of different age groups who reported to a diagnostic centre in Dhaka city. Pathogenic bacteria were isolated and identified from the collected samples following standard methods. Antibiotic sensitivity patterns of isolated bacteria were also determined by disc diffusion test. Proportion of UTI in female patients (71.67%) was found to be higher than the male (28.33%) patients and mostly caused by Escherichia coli (73.33%). Among Gram negative bacteria, E. coli (51%) was found to be predominant followed by Pseudomonas spp. (11.47%), Klebsiella (9.84%) and Salmonella Typhi (9.84%). Among Gram positive organism Staphylococcus aureus (9.0%), beta haemolytic streptococci (5.74%) and enterococci (3.28%) were found to be present. Among the tested antibiotics imipenem was found to be the most effective (93.02%) followed by gentamycin (76.03%) against all isolated bacteria. Amoxycillin was found to be least effective (21.29%) against all isolated bacteria. Increase in antibiotic resistance was possibly due to indiscriminate use of antibiotic for treatment of various infections. Prudent use of antimicrobial drugs will help reduce spread of resistant bacteria and complication of treatment of infected patients. Stamford Journal of Microbiology, Vol.9(1) 2019: 1-4